Cellulose 2019
DOI: 10.5772/intechopen.84531
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Cellulases: An Overview and Applications

Abstract: Cellulases are a complex group of enzymes which are secreted by a broad range of microorganisms including fungi, bacteria, and actinomycetes. In the natural environment, synergistic interactions among cellulolytic microorganisms play an important role in the hydrolysis of lignocellulosic polymer materials. In fact, it is the combined action of three major enzymes which determines the efficiency of this process. They are exoglucanases, endoglucanases, and β-glucosidase. Microorganisms produce these enzymes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(98 citation statements)
references
References 28 publications
1
93
0
4
Order By: Relevance
“…Cellulase is widely used in the textile and laundry detergent industries as it can play a part in the hydrolysis of cellulose and improve fabric properties for the textile industry and for cleaning textiles in the laundry detergent industry [154,280]. The food and beverage processing industries have used cellulase for the hydrolysis of cellulose during the drying of coffee beans and for the extraction of fruits and vegetables in juice production [281,282]. Cellulase, α-l-arabinofuranosidases and other glycosidases have also been used in brewery and wine production [213,277].…”
Section: Application Of Lignocellulolytic Enzymes In Bioprocessingmentioning
confidence: 99%
“…Cellulase is widely used in the textile and laundry detergent industries as it can play a part in the hydrolysis of cellulose and improve fabric properties for the textile industry and for cleaning textiles in the laundry detergent industry [154,280]. The food and beverage processing industries have used cellulase for the hydrolysis of cellulose during the drying of coffee beans and for the extraction of fruits and vegetables in juice production [281,282]. Cellulase, α-l-arabinofuranosidases and other glycosidases have also been used in brewery and wine production [213,277].…”
Section: Application Of Lignocellulolytic Enzymes In Bioprocessingmentioning
confidence: 99%
“…Achromobacter Previous studies have shown that natural cellulolytic strains degrade cellulose synergistically together with other microorganisms that utilize hydrolysates (such as glucose and cellobiose) as carbon and energy sources [2,10]. Furthermore, there might be a "jungle rule" in micro-ecosystems due to competition for carbon sources in the process of cellulose degradation, resulting in the shift of relative abundance among species [15].…”
Section: Dynamic Shifts In the Structure And Composition Of Cellulolymentioning
confidence: 99%
“…The major industrial applications of cellulases are as an additive in detergents, in food industry, textile industry, pulp and paper industry as well as in agriculture industry for controlling plant pathogens. The details of cellulase applications in various industries are presented in table 1 (Behera et al 2017;Jayasekara and Ratnayake 2019). In food industry, cellulase is widely used in the coffee processing and wine making due to its cellulolytic activity (Anoop Kumar et al 2018;Jayasekara and Ratnayake 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The details of cellulase applications in various industries are presented in table 1 (Behera et al 2017;Jayasekara and Ratnayake 2019). In food industry, cellulase is widely used in the coffee processing and wine making due to its cellulolytic activity (Anoop Kumar et al 2018;Jayasekara and Ratnayake 2019). Cellulase degrades the skin of the grape and along with it removes tannins and the unpleasant aroma (Claus and Mojsov, 2018).…”
Section: Introductionmentioning
confidence: 99%